Environmental Risk Controllability and Management of VOCs during Remediation of Contaminated Sites. Issue 1 (2nd January 2016) - Jia, Jianli; Wang, Bingbing; Wu, Yu; Niu, Zhao; Ma, Xiaoyan; Yu, Yan; Hou, Pin
ABSTRACT: The environmental risk controllability assessment system and its method of controlling volatile organic compounds (VOCs) during remediation of contaminated sites are established in this article based on soil vapor extraction (SVE) technology. According to the properties of VOCs and the technical and operational characteristics of the site remediation process, the environmental risk controllability index system includes environmental risk identification, risk source analysis, and risk assessment. Environmental risk management during site remediation was focused on technical control methods and engineering control technologies. Specifically, acceptance based on risk management was suitable for low-risk levels such as RRI3 and RRI4. Furthermore, control methods for high-level risk (RRI1 or RRI2) could be developed along with transformation and control, combined with the necessary emergency risk plan.